The Relevance Of Deep Strategic Management Improve Quality Education And Power Competition In University Bandar Lampung - Linda Wijayanti; Habiburahman Habiburahman (Cita konsultindo, 2024)
This research aims to investigate the conditions, analyze, implement and evaluate strategic management and its impact on improving the quality of education and competitiveness at Bandar Lampung University. The research method used is a descriptive qualitative method. The play subjects in this research were three students from the management study program at Bandar Lampung University. Data was collected through in-depth interviews, intensive observation and documentation techniques. Data analysis was carried out by compiling the results of in-depth interviews, intensive observation, and documentation systematic through data reduction, data presentation, and drawing conclusions. The research results show that there is a significant relationship between strategic management and education quality and competitiveness. Education quality is the play benchmarks in assessing the quality of an educational institution, which includes student achievement, teaching quality, and overall school programs. Therefore, the quality of education is the main indicator determining an institution's ability to compete in a competitive educational environment.